2017
DOI: 10.1093/brain/awx201
|View full text |Cite
|
Sign up to set email alerts
|

Using an engineered glutamate-gated chloride channel to silence sensory neurons and treat neuropathic pain at the source

Abstract: See Basbaum (doi:) for a scientific commentary on this article.Following nerve injury, sensory neurons become hyperexcitable and this is a key driver of neuropathic pain. Weir et al. develop a gene therapy approach that silences sensory neurons and reversibly normalizes pain thresholds in animal models of neuropathic pain. This new approach has significant translational potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 72 publications
(116 reference statements)
0
66
0
Order By: Relevance
“… 11 , 14 , 17 , 32 In fact, this transcription factor is currently considered as a nerve injury marker. 14 , 33 Actually, it has been speculated that ATF3 could contribute to formalin-induced long-lasting behavioral effects. 11 As expected, we found that nerve injury up-regulated ATF3 expression mainly in L5 and L6 DRGs and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 14 , 17 , 32 In fact, this transcription factor is currently considered as a nerve injury marker. 14 , 33 Actually, it has been speculated that ATF3 could contribute to formalin-induced long-lasting behavioral effects. 11 As expected, we found that nerve injury up-regulated ATF3 expression mainly in L5 and L6 DRGs and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results from DREADD studies hold great potential, but should be interpreted with caution and their future clinical use through gene therapy must control for certain risks. An alternative, but similar approach has recently been developed whereby viral transduction of an engineered chloride-channel sensitive to ivermectin (GluCl v2.0) was capable of long-term repeatable suppression of sensory neuron sensitivity and amelioration of neuropathic pain in rodents; the expression of GluCl v2.0 in human-induced pluripotent stem cell derived sensory neurones was also shown to cause their silencing in an ivermectin-dependent manner [ 38 ]. Overall, the ability to selectively control the excitability of neuronal subpopulations using either chemo- or optogenetic tools offers an attractive way of treating neuropathic pain compared to orally taken medications, which result in the whole body being exposed to the drug.…”
Section: Nociceptors: Transducers Of Painmentioning
confidence: 99%
“…Early methods involved the gene transfer using GAD65 using herpes simplex viral vectors to enhance inhibitory tone (Liu et al, 2004). More recent efforts have used the delivery of adeno-associated virus (AAV) containing glutamate activated chloride channels to peripheral neurons to promote long lasting pain relief by increasing hyperpolarizing GABA currents after ivermectin (designer drug) administration (Weir et al, 2017). Not all of these strategies will necessarily target neurons, delivery of anti-inflammatory cytokine IL-10 using lentiviral mediated transfer has also shown promise for neuropathic pain (He et al, 2013).…”
Section: Genetic Therapiesmentioning
confidence: 99%